A scoping review on the approaches for cannulation of reno-visceral target vessels during complex endovascular aortic repair. (3rd October 2022) - Grandi, Alessandro; D'Oria, Mario; Melloni, Andrea; Calvagna, Cristiano; Taglialavoro, Jacopo; Chiesa, Roberto; Lepidi, Sandro; Bertoglio, Luca
Abstract: OBJECTIVES: The aim of this study was to assess the approaches to reno-visceral target vessels (TVs) cannulation during branched-fenestrated endovascular aortic repair, determine the evidence base that links these approaches to clinical outcomes and identify literature gaps. METHODS: A scoping review following the PRISMA Protocols Extension for Scoping Reviews was performed. Available full-text studies published in English (PubMed, Cochrane and EMBASE databases; last queried, 31 June 2022) were systematically reviewed and analysed. Data were reported as descriptive narrative or tables, without any statistical analysis nor quality assessment. RESULTS: Fourteen retrospective articles were included. Seven articles studied the use of upper extremity access (UEA) during branched-fenestrated endovascular aortic repair, 3 studied the use of steerable sheaths and 4 included both approaches. A left UEA was used in 757 patients (technical success: 99%, stroke rate: 1–3%) and a right UEA in 215 patients (technical success: 92–98%, stroke rate: 0–13%). Seven studies (1066 patients) described a surgical access only (technical success: 80–99%, stroke rate: 0–13%), while 3 studies (146 patients) described a percutaneous access only (technical success: 83–90%, stroke rate: 3%) and lastly 4 studies compared UEA versus use of steerable sheaths from the transfemoral approach (TFA) (UEA: 563 patients, technical success: 95–98%, stroke rate: 1–8%; TFA: 209 patients, technical success: 98–100%, stroke rate: 0–1%). CONCLUSIONS: Both UEA and TFA as cannulation approaches were associated with high technical success and low perioperative complications. Currently, there is a paucity of high-quality data to provide definitive indication. Optimal UEA in terms of side (left versus right) and approach (surgical versus percutaneous) needs further study. Abstract : Over the last 2 decades, endovascular techniques have increasingly become the first-line treatment option for diseases in the paravisceral and thoraco-abdominal aorta, provided patients have suitable anatomy [1], mainly owing to their reduced invasiveness compared with classical open surgical repair.